2013
DOI: 10.1007/s12154-013-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

Alternative synthetic tools to phospho-specific antibodies for phosphoproteome analysis: progress and prospects

Abstract: Signal transduction cascades in living systems are often controlled via post-translational phosphorylation and dephosphorylation of proteins. These processes are catalyzed in vivo by kinase and phosphatase enzymes, which consequently play an important role in many disease states, including cancer and immune system disorders. Current techniques for studying the phosphoproteome (isotopic labeling, chromatographic techniques, and phosphospecific antibodies), although undoubtedly very powerful, have yet to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…2 Despite significant interest in drugs which act on protein kinases, [3][4][5][6][7] there are currently no catalytic synthetic methods for the site-selective phosphorylation of hydroxyl-containing amino acid residues. 2,8 Miller et al have reported the use of N-methyl histidinecontaining pentapeptide catalysts for asymmetric phosphorylation of inositol derivatives by phosphoryl chlorides, [9][10][11][12][13][14][15][16][17] e.g. in the synthesis of D-myo-inositol-1/3-phosphate 18 and for site-selective phosphorylation of teicoplanin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Despite significant interest in drugs which act on protein kinases, [3][4][5][6][7] there are currently no catalytic synthetic methods for the site-selective phosphorylation of hydroxyl-containing amino acid residues. 2,8 Miller et al have reported the use of N-methyl histidinecontaining pentapeptide catalysts for asymmetric phosphorylation of inositol derivatives by phosphoryl chlorides, [9][10][11][12][13][14][15][16][17] e.g. in the synthesis of D-myo-inositol-1/3-phosphate 18 and for site-selective phosphorylation of teicoplanin.…”
mentioning
confidence: 99%
“…These effects would be expected to lower the kinetic barriers both for initial nucleophilic addition of the N-oxide to the phosphoryl chloride and for subsequent substitution at phosphorus by the alcohol to regenerate the N-oxide, respectively during the catalytic cycle. 8 Using optimal catalyst 2l, a selection of bases were evaluated in place of the PPO for the transformation 1 -3, but with the reaction duration restricted to just 2 h (cf. 8 h in Table 1) to explore whether an increased rate of phosphorylation could be achieved without promoting subsequent elimination.…”
mentioning
confidence: 99%
“…In other words, a signal transduction map carries supra molecular interactions between different proteins, suggesting their potential physiological substrates, which use covalent modification mechanisms by phosphorylation in the majority of the processes. Once these processes are essential for the adequate cell development, knowing them becomes necessary [96,97].…”
Section: Peptides Microarrays As a Predictive Tool Of Cellular Metabomentioning
confidence: 99%
“…[2,3] Whilst several efficient non-enzymatic methods for the Lewis base (LB) catalysed [4] KR of alcohols via acylation, [5] silylation, [5,[6][7][8][9] phosphorylation [5,10,11] and sulfonylation [5,8,12] have been developed, analogous protocols for the KR of amines are less common. [5,13,14] This situation mainly reflects the challenge in achieving efficient catalysis, as most amines are themselves significantly Lewis basic.…”
mentioning
confidence: 99%